Concurrent sexual partnerships among married Zimbabweans – implications for HIV prevention - Mugweni E; Pearson S; Omar M (Dove Medical Press, 2015)
Esther Mugweni,1 Stephen Pearson,2 Mayeh Omar2 1UCL Department of Infection and Population Health, University College London, London, 2The Nuffield Centre for International Health and Development, University of Leeds, Leeds, UK Background: Concurrent sexual partnerships play a key role in sustaining the HIV epidemic in Zimbabwe. Married couples are at an increased risk of contracting HIV from sexual networks produced by concurrent sexual partnerships. Addressing these partnerships is an international HIV prevention priority. Methods: Our qualitative study presents the socioeconomic factors that contribute to the occurrence of concurrent sexual partnerships among married people in Zimbabwe. We conducted 36 in-depth interviews and four focus group discussions with married men and women in Zimbabwe in 2008 to understand the organizations of concurrent sexual partnerships. Data were analyzed using framework analysis. Results: Our study indicates that relationship dissatisfaction played a key role in the engagement of concurrent sexual partnerships. Depending on the source of the dissatisfaction, there were four possible types of concurrent sexual relationships that were formed: sex worker, casual partner, regular girlfriend or informal polygyny which was referred to as “small house”. These relationships had different levels of intimacy, which had a bearing on practicing safer sex. Participants described three characteristics of hegemonic masculinity that contributed to the sources of dissatisfaction leading to concurrent sexual activity. Similarly, various aspects of emphasized femininity were described as creating opportunities for the occurrence of concurrent sexual relationships. Economic status was also listed as a factor that contributed to the occurrence of concurrent sexual partnerships. Conclusion: Marital dissatisfaction was indicated as a contributing factor to the occurrence of concurrent sexual relationships. There were several reports of satisfying marital relationships in which affairs did not occur. Lessons from these marriages can be made part of future HIV prevention interventions targeted at preventing concurrent sexual partnerships by married couples. Keywords: concurrent sexual partnerships, HIV, marriage